The Analysis of Manufacturer Company’s Characteristics on Financial Disclosures and the Relation With Value Relevance - Malau, M (KnE Social Sciences, 2018)
The disclosure published in firms’ annual report is a very important factor for stakeholders in the capital market. The quality and quantity of information are different between different firms. The objective of this research is to investigate whether the firm’s characteristic determines the level of disclosures of financial measures and to study whether financial measures information have value relevance to the investor. Using a sample of 100 manufacturing firms in 2015 and applying panel data analysis, this study reports that the firm’s characteristics such as size, age, regulated company, product life cycle and leverage have significant effect on the disclosure level of financial measures. This research’s result also shows that financial measures have value relevance to investor. The higher the disclosure of financial measures, the stronger the effect on the earnings–return relationship (measured by earnings response coefficient, ERC), implying that the informativeness of earnings and financial measures disclosure are complementary to each other. Keywords: disclosure, financial measures, investor analysis, value relevance, earning response coefficient